2015
DOI: 10.1002/2014jb011703
|View full text |Cite
|
Sign up to set email alerts
|

The 2012 Mw 8.6 Wharton Basin sequence: A cascade of great earthquakes generated by near‐orthogonal, young, oceanic mantle faults

Abstract: We improve constraints on the slip distribution and geometry of faults involved in the complex, multisegment, M w 8.6 April 2012 Wharton Basin earthquake sequence by joint inversion of high-rate GPS data from the Sumatran GPS Array (SuGAr), teleseismic observations, source time functions from broadband surface waves, and far-field static GPS displacements. This sequence occurred under the Indian Ocean, ∼400 km offshore Sumatra. The events are extraordinary for their unprecedented rupture of multiple cross faul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
115
0

Year Published

2015
2015
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 99 publications
(125 citation statements)
references
References 99 publications
(214 reference statements)
10
115
0
Order By: Relevance
“…The M w 8.6 earthquake is the largest recorded intraplate event and also the largest recorded strike-slip event. Hill et al [2015] estimate an average stress drop of 17 MPa for this event. The Wharton Basin extends southeast of these events and has experienced other large, predominantly strike-slip earthquakes such as the 18 June 2000 M w 7.9 earthquake (Figure 1) west of the Investigator Fracture Zone [Robinson et al, 2001;Abercrombie et al, 2003].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…The M w 8.6 earthquake is the largest recorded intraplate event and also the largest recorded strike-slip event. Hill et al [2015] estimate an average stress drop of 17 MPa for this event. The Wharton Basin extends southeast of these events and has experienced other large, predominantly strike-slip earthquakes such as the 18 June 2000 M w 7.9 earthquake (Figure 1) west of the Investigator Fracture Zone [Robinson et al, 2001;Abercrombie et al, 2003].…”
Section: Introductionmentioning
confidence: 90%
“…The 11 April 2012 M w 8.6 and 8.2 great strike-slip earthquakes ( Figure 1) ruptured a mix of north-south and east-west trending strike slip faults in the Cocos Basin (north Wharton Basin) [e.g., Duputel et al, 2012;Satriano et al, 2012;Meng et al, 2012;Yue et al, 2012;Ishii et al, 2013;Wei et al, 2013;Hill et al, 2015], and there are many other strike-slip events along the outer rise ( Figure S1). The M w 8.6 earthquake is the largest recorded intraplate event and also the largest recorded strike-slip event.…”
Section: Introductionmentioning
confidence: 99%
“…Seismicity map is based on BMKG (Agency for Meteorology, Climatology and Geophysics) database (lower detection limit is approximately M w 4.5). b Coseismic offsets resulting from the April 11, 2012 earthquake derived from AGNeSS (blue arrows) and two previous studies (gray arrows) (Yadav et al 2013;Hill et al 2015). Ishii et al 2013).…”
Section: Resultsmentioning
confidence: 95%
“…Ishii et al 2013). Previous studies (Yadav et al 2013;Hill et al 2015) reported co-seismic offsets around the Andaman-Nicobar GNSS network, which includes the Sumatran GNSS Array (SuGAr) and IGS sites. The AGNeSS also observed horizontal co-seismic offsets ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation